2021
DOI: 10.18203/issn.2455-4510.intjresorthop20214964
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between anterior and posterior approach for bipolar hemiarthroplasty in intracapsular fracture neck of femur

Abstract: <ul><li><p class="abstract"><strong>Background:</strong> The present study was undertaken to to compare the efficacy of treatment of intracapsular neck of femur fracture operated by anterior and posterior approaches.</p><p class="abstract"><strong>Methods:</strong> A total 100 patients of either sex, aged &gt;65 years with intracapsular neck femur fracture were operated with hemiarthroplasty. The patients were divided into two equal groups and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results of this study demonstrate that the anterolateral Watson Jones approach for hip hemiarthroplasty is an effective and safe approach for treating femoral neck fractures in elderly patients. Demographic variables in the study such as average age of patient, sex distribution of the study population, side distribution of the fracture, energy associated with the underlying trauma were consistent with previous studies and were in close resemblance to study conducted by Aparajit et al [7] Duration of surgery was found to be comparable to that in previous conducted study by Juneja et al and was also lesser than what was required for posterior approach as found by the same study [8] . Mean intraoperative blood loss (142.67ml) was found to significantly lesser than in other study, by Wayan Subawa which has shown the mean blood loss to be 192.14ml in the anterolateral and 288.10 ml in posterior approaches respectively.…”
Section: Interpretation Of Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study demonstrate that the anterolateral Watson Jones approach for hip hemiarthroplasty is an effective and safe approach for treating femoral neck fractures in elderly patients. Demographic variables in the study such as average age of patient, sex distribution of the study population, side distribution of the fracture, energy associated with the underlying trauma were consistent with previous studies and were in close resemblance to study conducted by Aparajit et al [7] Duration of surgery was found to be comparable to that in previous conducted study by Juneja et al and was also lesser than what was required for posterior approach as found by the same study [8] . Mean intraoperative blood loss (142.67ml) was found to significantly lesser than in other study, by Wayan Subawa which has shown the mean blood loss to be 192.14ml in the anterolateral and 288.10 ml in posterior approaches respectively.…”
Section: Interpretation Of Resultssupporting
confidence: 87%
“…Duration of bed and hospital stays comparable to other studies. The functional outcomes, as measured by the Harris hip score, showed significant improvements at discharge, 1, and 6 months postoperatively [8] . Surgery through the anterolateral approach potentially leads to a reduction in operative trauma, less blood loss, smaller soft tissue wound, a reduction in postoperative pain, and earlier mobilization accomplished by preserving muscle insertions of gluteus medius and minimus.…”
Section: Interpretation Of Resultsmentioning
confidence: 85%